Open access epidemiologic data and an interactive dashboard to monitor the COVID-19 outbreak in Canada - Berry, Isha; Soucy, Jean-Paul R.; Tuite, Ashleigh; Fisman, David (Canadian Medical Association journal (CMAJ), 2020)
Berry et al highlight the critical need for timely, accurate and accessible epidemiologic data for the ongoing coronavirus disease 2019 (COVID-19) outbreak to inform public health response efforts. Individual-level case data are particularly valuable during outbreaks but are seldom made available in real time. Interactive data visualizations are also needed to contextualize this information and provide a pan-Canadian summary. These tools engage not only the public health and research communities but also the general public whose cooperation is essential to effectuate response efforts.